PERANCANGAN APLIKASI WEB SERVICE TOUR & TRAVEL PADA WEBSITE PARIWISATA SEMARANG STUDY KASUS DI ORYZA TOUR & TRAVEL (Information Technology and Telematics, 2013)
Abstract-- This study examines the exchange of  data between  Oryza  Tour  &  Travel  Website  with   Semarang Tourism Website using web service applications with NuSoap protocol.  The  problem  is   how  to  make  a  web  service applications that can share information between Oryza Tour & Travel Website with Tourism Website Semarang,  so  that users in Semarang Tourism Website can also see information held Oryza Tour & Travel Website.The  study  produced  a  web  application  service  with NuSoap protocol that has a function - a function that can be used to share data between Oryza Tour  &  Travel Website with Semarang Tourism Website. Through this system is expected to hopefully Oryza Tour & Travel can get more customers by displaying its  tourism packet  data  in  Semarang  Tourism   Website.  For  future improvement, complement and extend the functionality of the web service to plan the next steps.Keywords: Web Service, NuSoap, PHP, MySQL